2016
DOI: 10.32677/ijch.2016.v03.i03.017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, clinical, and hematological profile of sickle cell disease in South Rajasthan

Abstract: Objectives: To know the prevalence of sickle cell disease in 0-15 years old children of tribal area and to study its clinical and hematological profile. Materials and Methods: This cross sectional study was conducted between May 2014 and December 2015 in children below 15 years of age from tribal area of Sirohi and Udaipur district in South Rajasthan. Results: A total of 1090 children in tribal area were screened for sickle cell disease. Prevalence of sickle cell disease was found to be 8.53% of which 0.77% ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In homozygous cases, Mandot et al . [ 9 ] showed that 64% of people had musculoskeletal pain, 35% had abdominal discomfort, 7% had chest pain, and 71% had splenomegaly. Their hospital-based investigation could be the cause of the elevated occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In homozygous cases, Mandot et al . [ 9 ] showed that 64% of people had musculoskeletal pain, 35% had abdominal discomfort, 7% had chest pain, and 71% had splenomegaly. Their hospital-based investigation could be the cause of the elevated occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 36,752 students were screened and the prevalence of SCD/SCT was reported at the village level in the tribal sub-plan region of Rajasthan. Mandot and Ameta 22 screened a total of 1090 children belonging to Garasia tribe in Sirohi district of Rajasthan and the prevalence of sickle cell disorder reported by them was 8.53 per cent. Wherein 0.77 per cent were homozygous (HbSS) and 7.7 per cent were heterozygous (HbAS) which was comparatively lower than that in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Tribal groups with high prevalence of Hb-S (20-35%) include Bhils, Madiyas, Pawaras, Pardhans, and Otkars [42,43]. In India, apart from tribal individuals [44][45][46][47][48][49][50][51][52][53][54], red cell genetic disorders, such as abnormal Hbs, thalassaemia syndrome, and Glucose-6-phosphate dehydrogenase (G-6-PD) deficiency, have also been reported in various ethnic groups belonging to Scheduled Castes (SCs), Other Backward Castes (OBCs) and minorities including Muslim, Bohra-Muslim and Jain communities have also been reported in Rajasthan state [55][56][57][58][59][60][61][62][63][64][65][66][67]. In fact, this state has two distinct ecosystems arid or desert and humid where malaria is found to be hypo and hyperendemic, respectively.…”
Section: Sickle Cell Genes Among Tribal Peoplementioning
confidence: 99%